Using Alkaline Diet for Controlling Blood Acidosis (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2023)
The metabolism, biological and physiological processes in normal cells require keeping the blood pH within narrow limits (7.35 - 7.45). Blood acidosis is expressed as an increase in the concentration of acids in the blood or a decrease in the concentration of alkaline substances, which leads to a decrease in the blood PH from the ideal value (slight basal 7.35 - 7.45) and its conversion to acid values ​​less than PH 7. In which the acidity intensity increases The lower the pH value is less than PH, which lead to acids accumulate in the blood   or by the accumulation of carbon dioxide in the blood, which results from poor functions Lung or respiratory acidosis. Blood acidity is the main and primary factor for all diseases. To get rid off the negative effects of acidic foods, you should eat a lot of alkaline foods, vegetables and fruits. Eating them helps to provide the body with vitamins and minerals essential for health, which are used as buffers against acid-forming foods.